A systematic study of β-type Ti-based PVD coatings on magnesium for biomedical application - Zarka, M.; Dikici, B.; Niinomi, M.; Ezirmik, K. V.; Nakai, M.; Yilmazer, H. (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
A non-toxic and non-allergic beta-type Ti-29Nb-13Ta-4.6Zr (hereafter abbreviated as TNTZ) target material was prepared by the vacuum arc-melting process and then hot-forged, successfully. The TNTZ target has been deposited on the pure magnesium (Mg) and AZ31 Mg alloys by the physical vapor deposition (PVD) method. The characterization of the coatings was carried out by using SEM, EDS, AFM, and XRD techniques. The coating adhesion and its hardness were determined by scratch and Vickers tests, respectively. The corrosion resistance of the coatings was analyzed in simulated body fluid (SBF) under in-vitro conditions. Also, the coating wettability was compared by contact angle measurements. The results showed that the coatings had a very dense columnar and compact microstructure. The grain sizes were calculated between 20 and 40 nm, and the porosity of the coating was about 8.5% (+/- 1.5). The hydrophilicity of the Ti-based PVD coating was better than the uncoated Mg. The failure mechanism of the coating during the scratch test was formed as conformal cracks. The in-vitro corrosion tests indicated that the E-corr values of the TNTZ coated pure Mg and AZ31 alloy were nobler about 400 mV than the uncoated Mg-based samples. At the intensive stage of the corrosion, remarkable corrosion products, grown pits, and deep cracks were also observed on TNTZ-based coating layers due to the heavy corrosion attacks in SBF.
Keywords: TNTZ; PVD; beta-type Ti; Pure Mg; In-vitro corrosion; Characterization; MECHANICAL-PROPERTIES; CORROSION-RESISTANCE; TITANIUM-ALLOYS; ANTIBACTERIAL PROPERTIES; CYTOTOXICITY; FABRICATION; Materials Science; Physics